Nanocomposite membranes modified by graphene-based materials for anion exchange membrane fuel cells. Issue 17 (2nd February 2016) - Luo, Zhengyuan; Gong, Yujiao; Liao, Xiaofeng; Pan, Yongjun; Zhang, Hongwei
Abstract : Nanocomposite AEMs consisting of QPSF and GO or DGO showed improved alkaline solution stabilities. Abstract : Graphene oxide (GO) is synthesized through the oxidation reaction of graphite with strong oxidants and GO modified by dopamine (DGO) is also prepared via in situ self-polymerization of dopamine to form a polydopamine coating on the surface of GO. The GO or DGO is blended with chloromethylated polysulfone (CMPSF) in dimethylacetamide to prepare composite anion-exchange membranes (AEMs) by solution casting, followed by quaternization and alkalization. The synthesis of GO and DGO is confirmed by Fourier transform infrared attenuated total reflection. The properties of AEMs including their water uptake, thermal stability, mechanical property and ionic conductivity are investigated. Compared with the plain quaternized polysulfone membrane, the composite membranes containing 1% GO or 0.5% DGO display higher water uptakes, stronger tensile strengths, a bigger elongation rate at break and better alkaline solution stability. The ionic conductivities of them are 1.08 × 10 −2 S cm −1 and 1.07 × 10 −2 S cm −1 at 60 °C, respectively. Moreover, 86.9% and 76% of the two values can be maintained after the two composite membranes are treated in 1 M NaOH solution for 120 h at 50 °C.